2022
DOI: 10.1002/admt.202101665
|View full text |Cite
|
Sign up to set email alerts
|

Combining Vapor Phase Polymerization and Screen Printing for Printed Electronics on Flexible Substrates

Abstract: and have led to several commercial products such as inks, sensors, and displays.Conductive polymers can be synthesized by several methods, each with their own set of advantages and disadvantages. Chemical polymerization is the simplest method, requiring only the reagents necessary for the polymerization and a container, but generally results in poor properties. Electrochemical polymerization is a more controlled polymerization method (via the voltage and current), but requires a problematic three-electrode set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…From the previous report [ 18 ] we have developed an oxidant ink suitable for the VPP of EDOT, which was composed of 6 wt% Fe(Otf) and 37.5 wt% PEG‐PPG‐PEG in water. It was also shown that increasing the thickness, and therefore the absorbance, could be achieved by increasing the polymerization time of the VPP process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the previous report [ 18 ] we have developed an oxidant ink suitable for the VPP of EDOT, which was composed of 6 wt% Fe(Otf) and 37.5 wt% PEG‐PPG‐PEG in water. It was also shown that increasing the thickness, and therefore the absorbance, could be achieved by increasing the polymerization time of the VPP process.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that using VPP combined with screen printing allows for PEDOT to be formed without incorporation of the polymer into the ink. [ 18 ] Instead, the oxidant species (an iron salt) is formulated into an ink and after deposition by screen printing, the oxidant is exposed to a monomer vapor, and after a washing step the VPP film is ready for use in displays, transistors, or other printed electronic components. The combinations of screen printing and VPP, and the steps for the successful patterning of VPP conductive polymers, are outlined in Figure .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Printing technologies have evolved, providing a gradual improvement of the resulting printed circuits. The technologies for printing, such as screen printing [ 9 , 10 ], inkjet printing [ 11 ], or roll-to-roll printing [ 12 ], including flexography [ 13 , 14 ], gravure [ 15 , 16 ], or offset [ 17 ], have adapted to the needs of this kind of technology.…”
Section: Introductionmentioning
confidence: 99%